Perspectives on the transition toward green and climate neutral economies in Asia - Ordóñez de Pablos, Patricia 1975-; Mohammad Nabil Almunawar 1960-; Muhammad Anshari 1977- (IGI Global, 2023)
"Knowledge management and advanced information technologies such as AI, IoT, machine learning, and more can create digital tools and solutions to build more resilient, climate neutral, and green economies and societies. These digital tools and solutions and knowledge management can have a heavy impact on the achievement of sustainable development goals (SDGs) in Asia. Perspectives on the Transition Toward Green and Climate Neutral Economies in Asia offers innovative conceptual frameworks and theories, case studies, and empirical studies to understand how knowledge management and digital innovation can foster the transition towards more circular and climate neutral economies as well as greener economies in Asia. This book discusses how key and enabling digital tools and solutions and knowledge management can support the achievement of SDGs by 2030. Covering topics such as climate neutral economies, image recognition, and usability evaluation, this premier reference source is an excellent resource for deans, heads of departments, directors, politicians, policymakers, corporate heads, senior general managers, managing directors, librarians, students and educators of higher education, academicians, and researchers."--
Keywords: Economic development / Environmental aspects / Asia; Environmental policy / Asia; Environmental protection / Asia; Sustainable development / Asia